Tamarind (Tamarindus indica L.): Source of Ideas Behind the Semarang Batik Motifs to Strengthen Local Cultural Identity - Syakir, Syakir; Sobandi, Bandi; Fathurrahman, Moh.; Isa, Badrul; Anggraheni, Dini; Verayanti R., Sri (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2022)
Tamarind (Tamarindus indica L.), a type of tropical plant that grows in Indonesia has various benefits and has been widely studied by various disciplines. The study of Tamarind as a source of ideas for art creation, on the other hand, has not been widely carried out. The aims of this study are: (1) To explain the process of creating Semarang batik motifs using the idea of Tamarind through the stylization of forms; (2) to analyze the shape of the Tamarind batik motif to strengthen the identity of Semarang’s local culture. This study uses a qualitative approach with phenomenological methods to examine phenomena related to the creation process and the uniqueness of locality-based batik motifs on batik artisans in Semarang City. The data collection techniques used were observation, in-depth interviews, and document studies. The data that has been collected was analyzed interactively through data reduction, presentation, and conclusions with the scope of analysis in intra-aesthetic and extra-aesthetic studies. The results showed that: (1) Tamarind is a typical plant that is closely related to the toponym of the city of Semarang so it becomes a source of ideas for the creation of locality-based batik motifs through the stylization technique by Semarang batik artisans; (2) Visualization of the shape of the Tamarind batik motif that has been produced shows the diversity and uniqueness of the form as an aesthetic expression of the batik artisan in responding to the beauty of the natural and socio-cultural environment in Semarang City according to the level of knowledge and aesthetic experience. This research contributes to the batik artisan in exploring the diversity of local plant species as a source of ideas for creating environmentally-based batik motifs to strengthen the value of local cultural identity.